Підсумки інтродукції та селекції троянд у Національному ботанічному саду імені М.М. Гришка НАН України - Rubtsova, O.L.; Chizhankova, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Information on the beginning, methods and results of introduction and breeding of roses in M.M. Gryshko National Botanical Garden of the NAS of Ukraine is provided. Main sources of introduction of cultivars of Rosa L. are defined.Genofond collection of roses, that comprises 27 species, 11 forms and 470 cultivars and has the status of National property, is described by garden groups, countries of origin, colour of flowers and by the years of breeding. As a result it was defined that the distribution of cultivars by garden groups corresponds to the composition of world collection of roses, larger part of collection is comprised of cultivars of foreign origin. Main part of collection is composed by the tea-hybrid roses of pink color. Decorative indexes and biological features of cultivars breded by garden’s specialists, are shown. Main directions of further researches on introduction and selection of roses are outlined.